Simulation of hydrodynamics and convective heat transfer in microchannels - Minakov, Andrey Viktorovich; Lobasov, Aleksander Sergeevich; Dekterev, Aleksander Аnatolievich (Computational Continuum Mechanics, 2012)
The paper present the results of testing and adaptation of the universal CFD software package SigmaFlow applied to the problems of modeling isothermal fluid flow and heat transfer in microchannels. To simulate heat and mass transfer in microchannels, the classical methods of continuum mechanics based on the solution of the Navier–Stokes equations with slip boundary conditions at channel walls were used. Computational experiments confirmed the validity of the proposed approach for channel dimensions up to. In general, the test results are in good qualitative and quantitative agreement with the experimental data.
Keywords: microchannels; CFD; Navier-Stokes equations; control volume method